Direct and large-eddy simulation IX - Frohlich, Jochen; Kuerten, Hans; Geurts, Bernard J; Armenio, Vincenzo (Springer International Publishing, 2015)
This volume reflects the state of the art of numerical simulation of transitional and turbulent flows and provides an active forum for discussion of recent developments in simulation techniques and understanding of flow physics. Following the tradition of earlier DLES workshops, these papers address numerous theoretical and physical aspects of transitional and turbulent flows. At an applied level it contributes to the solution of problems related to energy production, transportation, magneto-hydrodynamics and the environment. A special session is devoted to quality issues of LES. The ninth Workshop on 'Direct and Large-Eddy Simulation' (DLES-9) was held in Dresden, April 3-5, 2013, organized by the Institute of Fluid Mechanics at Technische Universitèat Dresden. This book is of interest to scientists and engineers, both at an early level in their career and at more senior levels